In Vitro Antihemolytic Activity of Echinops spinosus Tannins Extracts against Human Erythrocytes - Kamila, Gheffour (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: In Algeria, especially in Tlemcen region, the research of medicinal plants with therapeutic uses presents a great interest. In this study, tannin extracts of the leaves, steams, and roots of Echinops spinosus which belong to the Asteraceae plant family of Tlemcen (north of Algeria) are screened for the antihemolytic activity toward human erythrocytes. The good results of the antioxidant activity of E. spinosus prompted us to lead a reflection on their antihemolytic activity. Materials and Methods: The hemolytic activity is performed by the modified spectroscopic method at five different inhibitory concentrations (IC50, 2 IC50, 10 IC50, 20 IC50, and 40 IC50) of each extract. Results: The aqueous extract of E. spinosus contains very significantly the highest quantity of tannins being 1910*** mg EC/100 g dry matter and 704.34*** mg EC/100g dry matter in the aerial part and roots, respectively. This result is very significant (P < 0.001). All the extracts exhibit a very low hemolytic activity that does not exceed 5% of hemolysis, except ethyl acetate and n-butanol extracts of roots which reach 35 and 40%, respectively, compared to the total hemolysis. Conclusion: This extracts have a good antihemolytic activity and are considered as safe to human erythrocytes.